Content and chemical composition of the essential oil of Myrcia lundiana Kiaersk In different drying times - Mércia Freitas Alves; Arie Fitzgerald Blank; Thiago Matos Andrade; Daniela Aparecida de Castro Nizio; Taís Santos Sampaio; Alberto Ferreira de Nascimento Junior (Bioscience Journal, 2018)
This study aimed to evaluate the effect of the leaves drying time on the content and chemical composition of the essential oil of M. lundiana. Treatments consisted of drying times of 0, 1, 2, 3, 4, 5, 6, 8, and 10 days, at 40o C, in a forced-air-circulation oven. Essential oils were obtained by hydrodistillation using the Clevenger apparatus, and chemical composition analysis was performed by GC-MS/FID. The drying process of M. lundiana leaves did not cause significant variations in the oil content, ranging from 1.18 to 1.51%. Nerolic acid was the major compound, ranging from 27.8% (at six days of drying) to 35.64% (at ten days of drying). The compound 1,8-cineole was identified as the second major compound of the essential oil, ranging from 9.04% to 14.01%. Other major compounds found in the essential oils were Î±-terpineol (7.12-8.41%), Î²-pinene (5.08- 9.03%), Z-Î±-trans-bergamotol (5.40-7.57%), and caryophyllene oxide (4.12-7.11%). One day of leaves drying at 40°C was sufficient to reach the recommended foliar moisture level without significantly altering the content and chemical composition of the essential oil of M. lundiana or the contents of the major compounds of the essential oil.